2017
DOI: 10.1016/j.stem.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Expansion and Folding in Human Cerebral Organoids

Abstract: An expansion of the cerebral neocortex is thought to be the foundation for the unique intellectual abilities of humans. It has been suggested that an increase in the proliferative potential of neural progenitors (NPs) underlies the expansion of the cortex and its convoluted appearance. Here we show that increasing NP proliferation induces expansion and folding in an in vitro model of human corticogenesis. Deletion of PTEN stimulates proliferation and generates significantly larger and substantially folded cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
280
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(311 citation statements)
references
References 49 publications
(76 reference statements)
17
280
1
Order By: Relevance
“…For example, the mechanisms underlying human cortical expansion and gyrification could be investigated with organoids. A recent report described expansion and surface folding of cerebral organoids following phosphatase and tensin homologue (PTEN) deletion and enhancement of the phosphoinositide 3-kinase (PI3K)–AKT growth signalling pathway 51 , suggesting that increased neural progenitor proliferation may be a major contributing factor to expansion and gyrification of the human brain. However, folding in the organoids was prominent in the neuroepithelium, and the relationship of this folding phenotype to actual cortical folding (which develops largely after neurogenesis ends and involves the cortical mantle rather than the proliferative zone) remains unclear.…”
Section: Organoids As Models Of Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the mechanisms underlying human cortical expansion and gyrification could be investigated with organoids. A recent report described expansion and surface folding of cerebral organoids following phosphatase and tensin homologue (PTEN) deletion and enhancement of the phosphoinositide 3-kinase (PI3K)–AKT growth signalling pathway 51 , suggesting that increased neural progenitor proliferation may be a major contributing factor to expansion and gyrification of the human brain. However, folding in the organoids was prominent in the neuroepithelium, and the relationship of this folding phenotype to actual cortical folding (which develops largely after neurogenesis ends and involves the cortical mantle rather than the proliferative zone) remains unclear.…”
Section: Organoids As Models Of Developmentmentioning
confidence: 99%
“…These manipulations are easily applied to organoid systems 51,66 , fuelling a burgeoning interest in the application of this technology to understand the pathophysiology of a wide range of adult and developmental human brain diseases. However, it remains to be seen if embryonic-stage organoids can be used to model neurodegenerative diseases of the ageing brain or neurodevelopmental diseases that manifest at later, postnatal stages.…”
Section: Organoids As Models Of Brain Diseasementioning
confidence: 99%
“…Cardinal features of ZIKV, of critical clinical importance are that (i) it is transmitted by a mosquito bite but can also be transmitted sexually, (ii) it is able to actively cross the placental barrier and replicate in the placenta, and (iii) it can disseminate to the fetus and its developing brain, where it leads to severe neurodevelopmental defects, in particular in the developing cortex, resulting in microcephaly. Studies of cell and tissue samples from infected humans, as well as experimentally infected NHP and mouse lines, have shown that ZIKV infects a wide variety of tissues and cells, including the skin (human dermal fibroblasts, epidermal keratinocytes, and immature dendritic cells) (Hamel et al, 2015), the testis (Leydig cells, sertoli cells, spermatogonia) (Govero et al, 2016; Ma et al, 2016), vaginal epithelium and uterine fibroblasts (Yockey et al, 2016; Chen et al, 2016), placenta (trophoblasts, endothelial cells, Hofbauer cells) (Noronha et al, 2016; El Costa et al, 2016; Simoni et al, 2017; Quicke et al, 2016), and the brain (cortical progenitors, mature neurons and astrocytes) (Gabriel et al, 2017; Li et al, 2017; Qian et al, 2016; Tang et al, 2016; Xu et al, 2016; Brault et al, 2016). It may also infect the eye (Ganglion cells, bipolar neurons, the optic nerve, cornea) and be found in body fluids including tears, saliva, semen, cervical mucus and urine (Miner et al, 2016a; Barzon et al, 2016; Zambrano et al, 2017).…”
Section: Mechanisms and Consequences Of Maternal-fetal Transmissionmentioning
confidence: 99%
“…Compared with monolayer cultures, 3-D neural tissues, named as brain organoids, provide unique opportunities to study neural development and to model neurological disorders (Quadrato et al, 2016). Recent studies identified human cell type-specific phenotypic changes during corticogenesis using brain organoid systems (Bershteyn et al, 2017; Li et al, 2017) and have studied the diversity of cell types generated during organoid development using large scale single cell analysis (Quadrato et al, 2017). …”
Section: Introductionmentioning
confidence: 99%